Social stratification and educational mobility: kesenjangan akses pada pendidikan tinggi - MA'RIFATUNNISA, MA'RIFATUNNISA MA'RIFATUNNISA (Maliki Interdisciplinary Journal, 2025)
This article discusses social inequality in the form of inequality in access to higher education. Higher education has been considered a key mechanism for social mobility and the reduction of structural inequalities in society. However, empirical reality shows that access to higher education is still strongly influenced by the socioeconomic background of the family. This article aims to examine and analyze the dynamics of social class and its impact on access to higher education in Indonesia. The results of previous research show that there is a significant correlation between family socioeconomic capital and access to higher education. Students from families with high socioeconomic status are 3.7 times more likely to access higher education than those from low-income families. Research also shows that social class affects not only initial enrollment but also the quality and sustainability of higher education. Students from low socioeconomic backgrounds typically face complex academic and economic challenges that will impact their academic success. Given this gap in access to higher education, it is important to have comprehensive policy interventions to reduce this gap, including equity-based scholarship programs, fair quota systems, and inclusive education funding. This article contributes to a comprehensive understanding of the reproduction of structural inequalities in the Indonesian education system and provides strategic recommendations for more comprehensive education policy interventions